Memo to Hyperborean Members - Roberts, Mark (New Age Movements, Occultism, and Spiritualism Research Library, 2023)
A memo or letter to members studying Hyperborea praising Pat Zook (Epona).
1 electronic record, digitized from original record. 1 PDF, 2 pages, 29.2 MB (30,663,996 bytes).
Keywords: Hyperborea (Wiccan sect); Roberts, Mark, 1934-2012--Correspondence; Epona (High priestess), 1951-2016; Business correspondence; Religious materials